La necesidad de reformar el código de la niñez y adolescencia, en relación a la edad mínima para el trabajo de los y las adolescentes - Galarza Núñez, Cesar Rodrigo (2015)
At present, children and adolescents workers represent a reality and a social problem that affects growing way to all the countries of America, conditions of childhood reveal deep, the quality of life of a society, the values of a country and its concern for the future. According to the report of the International Labour Organization (ILO) "the Elimination of child labour: a goal within reach, of May 2006, in the world, would have about 218 million children and adolescents aged between 5 and 17 working." 126 million are trapped in dangerous jobs and around 6millones, between 5 and 15 years, live in Latin America and the Caribbean In January 2003, the Ecuador adopted the code on children and adolescents, which provides for the prohibition of child labour and adolescent work-related rights. This code organizes the national system of comprehensive protection, provided by the Constitution of the Republic of Ecuador, articles 44, 45, 46 and 33, 34. The labour code and the code on children and adolescents are the most relevant standards concerning child labour, the labour code has been reviewed by the code on children in some of its parts, still need to reform them with an articulated that mention facing direct competition to protect childrenand adolescents from age 15 without dependency against economic exploitation and with those jobs that adversely affect their education, their health and their development. there a classification requiring implicitly the prevention, control and punishment of child labour without dependency from the 15 years therefore not to give solution to this legal vacuum will continue with labor exploitation to children and adolescents under 15 years of age, exposing them to dangers of any kind on the streets, constituting a sequel that will mark their lives and very difficult to be exceeded to develop as children, and adolescents according to their age being productive entities for the development of the Ecuador, therefore is suitable to reform the Art.82 regarding the age of working children and adolescents. In this context, the code on children and adolescents Ecuadorian there is a legal void where not has categorized work without dependence of children and adolescents up to age 15 without dependency ratio; and in the Labour Code nor is there a classification requiring implicitly the prevention, control and punishment of child labour without dependency from